Research advances of neutrophil-to-lymphocyte ratio in kidney diseases - Liang Chun-mei; Fu Ling (Linchuang shenzangbing zazhi)
Neutrophil-to-lymphocyte ratio （NLR） is a novel biomarker of systemic inflammation response.Attracting much attention in the fields of oncology，cardiovascular diseases and immune disorders，NLR is vital for predicting the diagnosis，treatment and prognosis.However，inflammation is involved in the pathophysiological processes of kidney diseases.Growing evidence indicates NLR is associated with kidney diseases.Here current understanding of NLR in kidney disease was summarized for providing useful rationales for basic researches and clinical strategies.